Intravenous thrombolysis for patients with in‐hospital stroke onset: propensity‐matched analysis from the Safe Implementation of Treatments in Stroke‐East registry. (5th October 2017) - Tsivgoulis, G.; Katsanos, A. H.; Kadlecová, P.; Czlonkowska, A.; Kobayashi, A.; Brozman, M.; Švigelj, V.; Csiba, L.; Fekete, K.; Kõrv, J.; Demarin, V.; Vilionskis, A.; et al.
Abstract : Background and purpose: Recent cross‐sectional study data suggest that intravenous thrombolysis (IVT) in patients with in‐hospital stroke (IHS) onset is associated with unfavorable functional outcomes at hospital discharge and in‐hospital mortality compared to patients with out‐of‐hospital stroke (OHS) onset treated with IVT. We sought to compare outcomes between IVT‐treated patients with IHS and OHS by analysing propensity‐score‐matched data from the Safe Implementation of Treatments in Stroke‐East registry. Methods: We compared the following outcomes for all propensity‐score‐matched patients: (i) symptomatic intracranial hemorrhage defined with the safe implementation of thrombolysis in stroke‐monitoring study criteria, (ii) favorable functional outcome defined as a modified Rankin Scale (mRS) score of 0–1 at 3 months, (iii) functional independence defined as an mRS score of 0–2 at 3 months and (iv) 3‐month mortality. Results: Out of a total of 19 077 IVT‐treated patients with acute ischaemic stroke, 196 patients with IHS were matched to 5124 patients with OHS, with no differences in all baseline characteristics ( P > 0.1). Patients with IHS had longer door‐to‐needle [90 (interquartile range, IQR, 60–140) vs. 65 (IQR, 47–95) min, P < 0.001] and door‐to‐imaging [40 (IQR, 20–90) vs. 24 (IQR, 15–35) min, P < 0.001] times compared with patients with OHS. No differences were detected in the rates of symptomatic intracranial hemorrhage (1.6% vs. 1.9%, P = 0.756), favorable functional outcome (46.4% vs. 42.3%, P = 0.257), functional independence (60.7% vs. 60.0%, P = 0.447) and mortality (14.3% vs. 15.1%, P = 0.764). The distribution of 3‐month mRS scores was similar in the two groups ( P = 0.273). Conclusions: Our findings underline the safety and efficacy of IVT for IHS. They also underscore the potential of reducing in‐hospital delays for timely tissue plasminogen activator delivery in patients with IHS.